2020
DOI: 10.1101/2020.10.01.321869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Torsin ATPases influence chromatin interaction of the Torsin regulator LAP1

Abstract: The inner nuclear membrane is functionalized by diverse transmembrane proteins that associate with nuclear lamins and/or chromatin. When cells enter mitosis, membrane-chromatin contacts must be broken to allow for proper chromosome segregation; yet how this occurs remains ill-understood. Unexpectedly, we observed that an imbalance in the levels of the lamina-associated polypeptide 1 (LAP1), an activator of ER-resident Torsin AAA+-ATPases, causes a failure in membrane removal from mitotic chromatin, accompanied… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…We found that mitochondria presenting HA-LAP1B NT or HA-LAP1B uNT on their surface could be strongly relocalised to the GFP-Lamin positive NE, whereas mitochondria expressing HA-LAP1C NT were less able to be relocated (Fig.6b, c). Consistent with the presence of a chromatin-binding domain in LAP1 B’s NT 40 , mitochondria presenting this region were strongly relocalised to the chromatin periphery. In all cases, expression of the HA-LAP1 N-termini on mitochondria induced their clustering, but mitochondria that did not relocalise to the NE were able to strongly recruit GFP-Lamin B1, but not GFP-Lamin A/C.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…We found that mitochondria presenting HA-LAP1B NT or HA-LAP1B uNT on their surface could be strongly relocalised to the GFP-Lamin positive NE, whereas mitochondria expressing HA-LAP1C NT were less able to be relocated (Fig.6b, c). Consistent with the presence of a chromatin-binding domain in LAP1 B’s NT 40 , mitochondria presenting this region were strongly relocalised to the chromatin periphery. In all cases, expression of the HA-LAP1 N-termini on mitochondria induced their clustering, but mitochondria that did not relocalise to the NE were able to strongly recruit GFP-Lamin B1, but not GFP-Lamin A/C.…”
Section: Resultssupporting
confidence: 63%
“…In all cases, expression of the HA-LAP1 N-termini on mitochondria induced their clustering, but mitochondria that did not relocalise to the NE were able to strongly recruit GFP-Lamin B1, but not GFP-Lamin A/C. We suggest that as well as containing a chromatin binding region 40 , the unique NT of LAP1B encodes a dominant lamin-binding domain that displays preference for B-type lamins.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…We expand the investigation of our device by demonstrating its application for two diverse applications, i.e., single-cell manipulation as well as microfluidic mixing. HeLa cells are a prominent model organism for biomedical as well as genetic research 29,30 and their controlled manipulation exposes great potential to allow for further insights on a single cell level. 3 The image sequence in Figure 4 solid-structure-based acoustic mixers.…”
Section: Single-cell Manipulation and Microfluidic Mixingmentioning
confidence: 99%
“…Some evidence also suggests that the ER surrounding spindle MTs serves as part of an organelle-exclusion 'spindle envelope' that spatially confines mitotic proteins to the spindle region (Schweizer et al, 2015). Persistent ER membrane contacts with mitotic chromosomes, but not with spindle MTs, have been associated with higher incidences of chromosome missegregation (Champion et al, 2019;Luithle et al, 2020;Schlaitz et al, 2013;Smyth et al, 2012). These studies suggest that the physical removal of ER membranes from mitotic chromosomes is necessary for accurate chromosome segregation; however, how the spatial reorganization of ER membranes and its clearance from the spindle region contributes to mitotic fidelity remains unknown.…”
Section: Introductionmentioning
confidence: 99%